HUBUNGAN EXSPLOSIVE POWER OTOT TUNGKAI DENGANHASIL LOMPAT JAUH PADA SISWA PUTRA KELAS X SEKOLAH MENENGAH KEJURUAN FARMASI IKASARI PEKANBARU - afriadi, Khairul; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem of this research is base on observation which was found by the researcher while do test of long jump male students in SMK Farmasi Ikasari Pekanbaru. Students did not anexpected result (3.60m). This it because is explosive power of leg muscle students grade X of SMK Farmasi Iksari Pekanbaru not good enough. Sampling used in this research is total sampling. Sample of this research is in the amount of 26 students. The instrument used in this research are standing broad jump to test the explosive power of the leg muscle and long jump to test the long jump itself. Data were analyzed statistically to test the normality with liliefors test on the significant level of =0,05. Value of variable X withL0maks = 0,0905 < Ltabel = 0,173 and variable of Y L0maks = 0,0848 < Ltabel = 0,173, in conclusion value of data X and Y are normal distribution. Based on the analysis data, it is obtained that the correlation of X and Y is rcount = 0,662 from rtable = 0,396. The correlation of variable to another variable is determined by rcount> rtable. There is a significant correlation between the explosive power of the leg muscle to the long jump results of X grade male students of SMK Farmasi Ikasari Pekanbaru.Keywords: Explosive Power Of Leg Muscle, Long Jump.